Yona of the dawn. 22 - Kusanagi, Mizuho, 1979-; MacFarlane, Ysabet Reinhardt (VIZ Media, LLC, 2020)
Princess Yona lives an ideal life as the only princess of her kingdom. Doted on by her father, the king, and protected by her faithful guard Hak, she cherishes the time spent with the man she loves, Su-won. But everything changes on her 16th birthday when tragedy strikes her family! The mission to rescue Yona and Riri from Sei leads to reunions and revelations! Who is Riri<U+2019>s secret crush? And has Yona come to realize her feelings for Hak? Later, masked visitors from the nation of Xing beckon Yona and the Dragon Warriors to meet their leader!